Structural reforms, technological gaps and economic development : Latin American perspective - Cimoli, Mario (ECLAC SantiagoCL, 2002)
Explores the impact recent structural reforms have had on the following: macro-to-micro linkages; the pattern of production specialization; the entry and exit of firms during the adjustment process; and the sources of technical change in the present more open and de-regulated Latin American scenarios.